2020
DOI: 10.1016/j.apor.2020.102331
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing climate resilience of vertical seawall with retrofitting - A physical modelling study

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…As originally proposed by Franco et al (1994) and Van der Meer and Janssen (1995), and later confirmed in physical and numerical investigations of wave overtopping (see for example, ; Hughes et al (2012); Zanuttigh et al (2013); Abolfathi et al (2018); Salauddin and Pearson (2018); Dong et al (2018Dong et al ( , 2020; Pearson (2019a, 2020)), the distribution of individual overtopping volumes at conventional sea defences follow a two-parameter Weibull distribution function, as follows:…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…As originally proposed by Franco et al (1994) and Van der Meer and Janssen (1995), and later confirmed in physical and numerical investigations of wave overtopping (see for example, ; Hughes et al (2012); Zanuttigh et al (2013); Abolfathi et al (2018); Salauddin and Pearson (2018); Dong et al (2018Dong et al ( , 2020; Pearson (2019a, 2020)), the distribution of individual overtopping volumes at conventional sea defences follow a two-parameter Weibull distribution function, as follows:…”
Section: Introductionmentioning
confidence: 70%
“…In a sequence of overtopping events, coastal engineers and practitioners are generally interested in the largest wave by wave overtopping volumes. Consequently, the Weibull shape parameter, b, is usually calculated from the gradient of the extreme tail of the Weibull distribution where only the largest volumes reside on the Weibull scale (see for example, Pearson et al, (2002); Dong et al, (2018Dong et al, ( , 2020; Pearson (2018, 2020)). In Fig.…”
Section: Weibull Plots Of Wave-by-wave Overtopping Volumesmentioning
confidence: 99%
“…Over the years, many physical and numerical modelling research has been carried out to investigate the wavestructure interactions and the resulting mean overtopping characteristics at sea defences (e.g., Franco et al, 1994;Van der Meer and Bruce, 2014;Abolfathi et al, 2016 andDong et al, 2018 and2020;Yeganeh-Bakhtiari et al, 2017 and2020;Fitri et al, 2019;Pearson, 2019 and2020). The most reliable empirical predication formulae for prediction of mean overtopping rates have been reported in the overtopping manual, EurOtop (2018).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the incident wave heights in relatively deep waters follow the Rayleigh distribution whereas in nearshore regions, the distribution of incident wave heights deviates from the Rayleigh distribution (Battjes and Groenendijk, 2000;Goda, 2009;EurOtop, 2018;Dong et al, 2020b). The Rayleigh distribution of wave heights can be expressed as:…”
Section: Incident Wave Heightsmentioning
confidence: 99%